Developing a 4-dimensional interdisciplinary learning environment for construction industry professionals : Final Report. - Landorf, Chris; Brewer, Graham; Ward, Stephen (Office for Learning and Teaching, 2016)
Increasing student numbers and concerns about safety on building sites have contributed to reduced access to live project sites for students in construction related professional disciplines. Contextualising the application of abstract knowledge to practical reality within this context is a constant challenge, particularly given the interdisciplinary nature of the construction industry. Three Universities collaborated on this project across four construction related professions- architecture, construction management, engineering and building surveying. The project established a suite of interactive and interdisciplinary problem-based learning activities that address this issue using 4-dimensional time-lapse digital images captured during the construction of the University of Queensland's Advanced Engineering Building. This interactive learning environment, together with the instructional activities and assessment methods developed to test the effectiveness of that environment, will form the basis of a construction library that can be expanded to over time with the view to it becoming a catalogue of different building types, construction methods and environmental conditions.